2015
DOI: 10.1080/09593330.2015.1055817
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of food waste into biofertilizer for the biocontrol of root knot nematode by Paecilomyces lilacinus

Abstract: The feasibility of converting food waste into nematocidal biofertilizer by nematophagous fungus Paecilomyces lilacinus (P. lilacinus) was investigated. The culture conditions of P. lilacinus were optimized through response surface methodology. Results showed that fermentation time, the amount of food waste, initial pH and temperature were most important factors for P. lilacinus production. The P. lilacinus production under optimized conditions was 10(9.6 ± 0.3) conidia mL⁻¹. After fermentation, the chemical ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Sharma et al (2014) found that the mortality of M. incognita J2s was increased to 100% if the nematode pathogenic strain P. lilacinus 6029 was fermented on the medium of Karanja cake than the Czapeck-Dox filtrate under the fermentation parameters of a lower pH and 15 days' incubation time. It was also found that the fermentation parameters of incubation time, initial pH, and temperature were the most important factors for biocontrol of root knot nematodes by P. lilacinus production (Yu et al, 2015). Based on single-factor experiments and the Plackett-Burman design experiments, the optimal fermentation parameters of the MM + wheat bran-2 medium were an initial pH of 6, fermentation temperature at 28 • C, rotating speeds at 180 rpm, fermentation media volume of 60 ml, inoculum volume of 1 ml, and incubation for 7 days.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sharma et al (2014) found that the mortality of M. incognita J2s was increased to 100% if the nematode pathogenic strain P. lilacinus 6029 was fermented on the medium of Karanja cake than the Czapeck-Dox filtrate under the fermentation parameters of a lower pH and 15 days' incubation time. It was also found that the fermentation parameters of incubation time, initial pH, and temperature were the most important factors for biocontrol of root knot nematodes by P. lilacinus production (Yu et al, 2015). Based on single-factor experiments and the Plackett-Burman design experiments, the optimal fermentation parameters of the MM + wheat bran-2 medium were an initial pH of 6, fermentation temperature at 28 • C, rotating speeds at 180 rpm, fermentation media volume of 60 ml, inoculum volume of 1 ml, and incubation for 7 days.…”
Section: Discussionmentioning
confidence: 97%
“… Sharma et al (2014) found that the mortality of M. incognita J2s was increased to 100% if the nematode pathogenic strain P. lilacinus 6029 was fermented on the medium of Karanja cake than the Czapeck–Dox filtrate under the fermentation parameters of a lower pH and 15 days’ incubation time. It was also found that the fermentation parameters of incubation time, initial pH, and temperature were the most important factors for bio-control of root knot nematodes by P. lilacinus production ( Yu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compost can be utilized as fertilizer and energy fuel, promoting circular economy, and optimizing composting process and composter can mitigate the environmental impacts (Liu et al, 2018;Chia et al, 2020). Paecilomyces lilacinus has protease activity and nematocidal ability which can convert food waste into nematocidal biofertilizer (Yu et al, 2015). Zhao et al (2019) highlighted the necessity of location-suitable and urban-rural recycling nitrogen management strategies for reducing the risk of nitrogen emission from household food consumption in China.…”
Section: Urban Food Waste Compostingmentioning
confidence: 99%